Academic perception on the relationship between study group participation and evaluation performance (Research, Society and Development, 2020)
The race for higher education training has grown and, as a result, it has become necessary for students to constantly seek strategies that will make learning more meaningful, with the study group being an option. Thus, this study aims to analyze the perception of academics about the relationship between participation in study groups and performance in assessments. This is a cross-sectional, descriptive study with a quantitative approach. The same was carried out with academics regularly enrolled in the Physiotherapy course of a private higher education institution. And the data collection took place through a questionnaire containing objective questions, using the Google Forms online platform. As a result, it was observed that academics attach considerable importance to participation in study groups as a way to improve their knowledge through mutual exchange of knowledge and constant encouragement to study. However, there was a reduction in dedication to studies in the remote modality, when compared to the face-to-face modality, as well as an increase in the negative perception about academic performance. We emphasize the importance of adopting future strategies that further minimize the challenges inherent to higher education and that encourage students to seek to dedicate themselves to study, regardless of the teaching modality. Study groups, therefore, become an instrument of interaction that can facilitate this learning process for academics to obtain a good performance in assessments.